Subjectification and the Croatian dative - Stanojević, Mateusz-Milan (2008)
There have been quite a few analyses of the dative case in the cognitive linguistic framework in Slavic languages (e.g. Polish (Dąbrowska 1997) ; Czech (Janda 1993)) and other languages (e.g. Spanish (Maldonado 2002)). All descriptions basically hinge on the notion of the dominion. This type of description is also applicable to Croatian (Stanojević and Geld 2008). A typical example of the Croatian dative involves transfer (of a physical or an abstract entity) from the dominion of the agent to dominion of the dative. Thus, in (1) potpora ? support? is transferred to the dominion of the dative nova Vlada ? the new government? : (1) Također je data potpora novoj Vladi (...) Also is given support new-DAT Government-DAT ? Support was also given to the new government.? However, the dative also spans such usages as emotional involvement (in (2)), and many others: (2) Stidi se da si mi ovakav kostriš i divljan Shame REFL that are I-DAT such disheveled and rough ? You should be ashamed of yourself, that you are so disheveled and rough (to me)? This paper explores whether subjectification, which has been suggested as the organizing principle of the Spanish dative (Maldonado 2002), may be advantageously used in an account of the Croatian dative. If subjectification is indeed one of the organizing principles of the Croatian dative, this should be reflected in different tendencies of the use of nouns and pronouns in the dative. Nouns (which do not include the speaker) should primarily be used in objective arrangements, and pronouns (which may include the speaker) should exhibit a greater tendency towards subjective arrangements. In order to test this claim, we performed a corpus study of all the dative nouns and pronouns in the tagged section of the Croatian National Corpus (CNC), and an analysis of a random sample of the pronoun mi and meni ? I-DAT? (which should exhibit the greatest degree of subjectification) from the entire CNC. We divided the various uses into groups according to semantic and structural criteria. The results show that mi and meni have roughly 40% of subjective usages, while subjective uses in all other pronouns amount to roughly 25% of all occurrences. In contrast, nouns exhibit less than 5% of subjective usages, which confirms our hypothesis. In other words, the semantic category of the dative in Croatian exhibits a continuum between objective and subjective datives. The two poles of the continuum roughly correspond to the traditional distinction between the free and governed datives. Example (1) is an objective (and governed) dative, whereas (2) is subjective and free. Furthermore, while the subjectification description unifies all synchronic usages, it may also be used to account for the diachronic development and it fits in well with cross-linguistic Slavic (and non-Slavic) data. Selected references Dąbrowska, E. 1997. Cognitive Semantics and the Polish Dative. Berlin, New York: Mouton de Gruyter Janda, L. 1993. A Geography of Case Semantics: The Czech Dative and the Russian Instrumental. Berlin: Mouton de Gruyter Langacker, R. W. 1990. Subjectification. Cognitive Linguistics 1. 5-38. Maldonado, R. 2002. Objective and subjective datives. Cognitive Linguistics 13 (1), 1-65 Stanojević, M.-M. and R. Geld. 2008. The dative in Croatian as a dominion phenomenon. Etudes cognitives 8, 95-108